2011
DOI: 10.1007/s10008-011-1543-0
|View full text |Cite
|
Sign up to set email alerts
|

Titanium phosphates as positive electrode in lithium-ion batteries: composition, phase purity and electrochemical performance

Abstract: Titanium phosphate materials were synthesized by evaporation-induced self assembly method by using Ti(OC4H9)(4) and PCl3, in the presence of Pluronic (P123) as a non-ionic surfactant template. The molar ratios of P/Ti and the heat treatment of the materials affected their structures, particle geometries and electrochemical performances as indicated by X-ray powder diffraction, thermal gravimetric analysis, scanning electron and transmission electron microscopy and other electrochemical techniques. As expected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 70 publications
4
3
0
Order By: Relevance
“…The band at 953 and 1190 cm −1 corresponded to the valence vibration of P–O–P bridge and the asymmetric vibration of P–O, respectively. While the band at 1038 cm −1 is assigned to the stretch of Ti–O–P skeleton similar to this reported by Attia et al 43 who suggested the heat treatment (>500 °C) can transform phosphoric acid in the presence of TiO 2 to titanium pyrophosphate (TPP) or other phosphate derivatives. 43–45 This result confirms the presence of titanium pyrophosphate corroborating the PXRD analysis.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The band at 953 and 1190 cm −1 corresponded to the valence vibration of P–O–P bridge and the asymmetric vibration of P–O, respectively. While the band at 1038 cm −1 is assigned to the stretch of Ti–O–P skeleton similar to this reported by Attia et al 43 who suggested the heat treatment (>500 °C) can transform phosphoric acid in the presence of TiO 2 to titanium pyrophosphate (TPP) or other phosphate derivatives. 43–45 This result confirms the presence of titanium pyrophosphate corroborating the PXRD analysis.…”
Section: Resultssupporting
confidence: 83%
“…While the band at 1038 cm −1 is assigned to the stretch of Ti–O–P skeleton similar to this reported by Attia et al 43 who suggested the heat treatment (>500 °C) can transform phosphoric acid in the presence of TiO 2 to titanium pyrophosphate (TPP) or other phosphate derivatives. 43–45 This result confirms the presence of titanium pyrophosphate corroborating the PXRD analysis. 46…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Asymmetric stretching vibrations of NH 4 + and C–H groups are observed at wave numbers 3200 cm –1 and 3045 cm –1 , respectively, in the organic complex and obtained sample [ 48 , 49 ]. The band at 1630 cm –1 corresponds to bending vibrations of internal O–H bonds [ 50 , 51 ]. Organic residues of mandelic acid remain embedded in the double oxide microstructure: characteristic bands at 1450 and 1403 cm –1 refer to H–C–O scissor and C–O–C asymmetric stretching vibration, while the peaks at 1185 cm –1 and 944 cm –1 common for all samples are attributed to the C–H bond [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rechargeable lithium ion batteries (LIBs) are considered as the most promising power sources for emerging portable electric vehicles and renewable power stations. [1][2][3][4][5][6] Massive efforts have been made to develop advanced electrode materials with high power density, long cycle stability, and practical reliability. [7][8][9][10] TiO 2 is one of the most attractive anode materials because of its high safety and outstanding stability.…”
Section: Introductionmentioning
confidence: 99%